DIAGNOSTICS OF POLYCULTURAL COMPETENCE OF FUTURE TEACHERS - O. G. Smolyaninova; V. V. Korshunova; Ya. M. Dayneko (Образование и наука)
Introduction. Nowadays, repeatedly increasing migration flows connected with labor international migration and cocurrent frequent ethnic conflicts directly touched upon the education as intolerance to representatives of other cultures is most considerably shown among youth. Taking into account those processes, the problem of teachers’ training capable to cope with their professional duties in the conditions of ethnic and religious variety is brought into focus. Polycultural competence of the professional standard of the teacher is counted as a basic one. At the same time, the components of polycultural education are insufficiently fully and accurately registered in obligatory results of development of the main programs of pedagogical specialties.The aim of the present publication is to discuss the need of subject content changes of teachers’ vocational training at Federal University taking into account the specifics of the multinational regional environment and justification of expediency of regular diagnostics development of polycultural competence among future teachers for dynamics tracking of the planned personal new growths and their timely correction.Methodology and research methods. The research is based on cross-cultural, theoretical and activity-based studies as the most relevant ones for the present stage of professional and pedagogical training. Theoretical and empirical methods of studying of formation of components of poly-cultural competence of students are used; interviewing and questioning of students, methods of quantitative-qualitative and content analysis are applied.Results and scientific novelty. The experience of complex diagnostics of level of polycultural competence of students of pedagogical specialties of the Siberian Federal University is presented (Krasnoyarsk). The analysis of monitoring results served as basis for creation of the model of components formation of this competence which is obligatory for a teacher carrying out the professional activity in the multinational and multireligious environment. The mechanisms of the organization of development of poly-cultural competence are described at the target, substantial, personal, strategic, organizational and technological levels.Practical significance. The research materials will be useful for educators to improve the quality of teacher training in terms of multicultural competence formation; school teachers working in multinational classes with migrant children whose training requires not only knowledge of the subject, but also the ways of socialization judging from national or religious specifics.